Building Destination Competitiveness Through Memorable Tourism Experience - Ika Barokah Suryaningsih; Kristian Suhartadi Widi Nugraha; Juan Firman Ramadhani (Universitas Negeri Semarang, 2023)
Destination competitiveness is a challenge for the development of tourist attractions. Tourist destinations do not only discuss what attractions tourists can enjoy but are more broadly interpreted as what tourists can experience. This research aims to prove the mediating role of memorable tourism experiences on the relationship between tourist perception and destination competitiveness. The population in this study were tourists who were travelling or had travelled to the Ijen Blue Fire Crater. The population in this study is infinite because valid data was not obtained. The sampling technique used was the purposive sampling method with 150 respondents. The analytical tool used in the research is SEM-PLS with SmartPLS 4 software. The research results prove that tourists' perceptions have a positive and significant effect on the memory tourism experience, and the memory tourism experience has a positive and significant impact on the destination's competitiveness. The urgency of this study is an essential experience for tourists in determining their desire to visit a destination repeatedly. Thus, this research shows that destination competitiveness can be built with methods that arouse emotions and influence tourists with triggers from memorable tourist experiences.